THE ROLE AND IMPORTANCE OF THE NEW VERSION OF THE "LAW ON EDUCATION" IN THE TRAINING OF PEDAGOGICAL PERSONNEL - Shodiyeva Aziza Zakir kizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: In this article, the role of the new edition of the law on education in the training of pedagogical personnel and the improvement of the quality of education and the results achieved in the field of education are scientifically analyzed.